2011
DOI: 10.1002/app.34058
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and absorption intensity analyses of Er2O3 nanoparticles suspended in polymethyl methacrylate

Abstract: Nanoparticles suspended in polymeric host materials are found to have tremendous potential for various photonic and biological applications due to their unique material properties. Polymethyl methacrylate (PMMA) is known to be one of the best vinyl polymers owing to its excellent dimensional quality, weather resistance, easiness of synthesis, resistance to laser damage, and high mechanical strength. In this article, we describe a methodology to fabricate thin discs of nanocrystalline erbium oxide (Er 2 O 3 ) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Various studies reported the impact of using Er 2 O 3 as a nanofiller on the properties of various polymer nanocomposites. For example, the addition of Er 2 O 3 nanoparticles was shown to improve the electrical, thermal and optical properties of PMMA polymers [ 19 ]. Similarly, the electrical conductivity of CMC/PVA was observed to be enhanced after the addition of Er 2 O 3 nanoparticles [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies reported the impact of using Er 2 O 3 as a nanofiller on the properties of various polymer nanocomposites. For example, the addition of Er 2 O 3 nanoparticles was shown to improve the electrical, thermal and optical properties of PMMA polymers [ 19 ]. Similarly, the electrical conductivity of CMC/PVA was observed to be enhanced after the addition of Er 2 O 3 nanoparticles [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its visible transparency, PMMA is a convenient host for optically active NPs. In fact, fluorescent NPs have been dispersed in bulk PMMA [26,27]. However, this approach supposes a small surface/volume ratio that limits the physical interaction of the NPs with the surrounding medium and hampers particle release.…”
Section: Introductionmentioning
confidence: 99%